ORIGINAL PRACTICE DEVELOPMENT AND RESEARCH Enabling nursing students to have a voice in designing a learning resource to support their participation in a clinical placement. (17th November 2021) - Mackay, Maria; Jans, Carley; Dewing, Jan; Congram, Alicia; Hoogenboom, Louise; King, Tanya; Kostiainen, Daniel; McCarthy, Ionna
No abstract available